Crohn's disease and ulcerative colitis are associated with different lipid profile disorders: a nationwide population‐based study. Issue 4 (6th November 2019) - Soh, Hosim; Im, Jong Pil; Han, Kyungdo; Park, Seona; Hong, Seung Wook; Moon, Jeong Min; Kang, Eun Ae; Chun, Jaeyoung; Lee, Hyun Jung; Kim, Joo Sung
Summary: Background: The relationships between lipid profiles and IBD remain elusive. Aim: To determine the association of IBD with serum lipid profiles. Methods: A nationwide population‐based study was performed using claims data from the Korean National Healthcare Insurance service. A total of 9 706 026 subjects undergoing medical check‐ups in 2009 were enrolled and followed up until 2016. Individuals who developed Crohn's disease (CD) or ulcerative colitis (UC) were identified during follow‐up. Adjusted hazard ratio (aHR) by age, sex, body mass index, cigarette smoking, alcohol drinking, exercise, income and underlying comorbidities was calculated to define the impact of serum lipid profiles on developing IBD. Results: During a median follow‐up of 7.3 years, IBD was detected in 7, 058 (0.07%) individuals. Compared with the highest quartile of serum total cholesterol (TC) levels, lower TC levels were associated with higher incidence of CD (aHR: Q1, 2.52; Q2, 1.52; Q3, 1.27), but not UC. Lower serum LDL‐C levels were associated with higher incidence of CD (aHR: Q1, 1.92; Q2, 1.47; Q3, 1.22), but not UC. Moreover, lower serum HDL‐C levels were associated with higher incidence of CD (aHR: Q1, 2.49; Q2, 1.90; Q3, 1.43), but not UC. In contrast, lower serum triglyceride levels were associated with higher incidence of UC (aHR: Q1, 1.22; Q2, 1.19; Q3, 1.19), but not CD. Conclusions: Low serum TC, LDL‐C and HDL‐C levels were associated with CD. Low serum triglyceride levels were related to UC.